Sampling Volatile Organic Compound Emissions from Consumer Products: A Review - Haug, Helen; Klein, Luise; Sauerwald, Tilman; Poelke, Birte; Beauchamp, Jonathan; Roloff, Alexander (Critical Reviews in Analytical Chemistry, 2022)
Volatile organic compounds (VOCs) are common constituents of many consumer products. Although many VOCs are generally considered harmless at low concentrations, some compound classes represent substances of concern in relation to human (inhalation) exposure and can elicit adverse health effects, especially when concentrations build up, such as in indoor settings. Determining VOC emissions from consumer products, such as toys, utensils or decorative articles, is of utmost importance to enable the assessment of inhalation exposure under real-world scenarios with respect to consumer safety. Due to the diverse sizes and shapes of such products, as well as their differing uses, a one-size-fits-all approach for measuring VOC emissions is not possible, thus, sampling procedures must be chosen carefully to best suit the sample under investigation. This review outlines the different sampling approaches for characterizing VOC emissions from consumer products, including headspace and emission test chamber methods. The advantages and disadvantages of each sampling technique are discussed in relation to their time and cost efficiency, as well as their suitability to realistically assess VOC inhalation exposures.
CRIS-Team Scopus Importer:2022-11-11
Keywords: Emission test chamber; headspace; indoor air quality; inhalation exposure; VOCs